Indoleamine 2,3-dioxygenase 1 promotes osteosarcoma progression by regulating tumor-derived exosomal miRNA hsa-miR-23a-3p - Yang, Dan; Chen, Yinxian; He, Zhen Ning Tony; Wang, Yichen; Ke, Chenghui; Luo, Yi; Wang, Sun; Ma, Qichao; Chen, Mengjie; Yang, Qing; Zhang, Ziming (Frontiers in Pharmacology, 2023)
Background: Osteosarcoma (OS) is the most common primary malignant tumor originating in bone. Immunosuppressive enzyme indoleamine 2,3-dioxygenase 1 (IDO1) participates in tumor immune tolerance and promotes tumor progression, while the study of IDO1 in OS is limited. Methods: Immunohistochemistry analysis was performed to test the expression of IDO1 and Ki67. The relationship between IDO1 or Ki67 positive count and clinical stage of the patient was analyzed. Laboratory test indexes including serum alkaline phosphatase (ALP), lactate dehydrogenase (LDH), white blood cell (WBC) count and C-reactive protein (CRP) at diagnosis of OS patients were collected. The relationship between positive count of IDO1 and Ki67 or laboratory test indexes was analyzed by Pearson’s correlation analysis. IDO1 stably overexpressed cell lines of these cells (MG63 OE, 143B OE and hFOB1.19 OE) were constructed and validated by Western blot and Elisa. Exosomes were isolated from conditioned culture media of these cells and were identified by Zetaview nanoparticle tracking analyzer. Next-generation sequencing was conducted to identify miRNAs enriched in exosomes. Differentially expressed miRNAs (DE miRNAs) were verified in clinical samples and cell lines by qPCR. Biological processes and cell components analysis of DE miRNAs was conducted by GO enrichment analysis using the protein interaction network database. Results: Immunosuppressive enzyme IDO1 was highly expressed in tumor tissues. 66.7% (6/9) of the tissues showed moderately or strongly positive immunostaining signal of IDO1, and 33.3% (3/9) were weakly positive. The expression of IDO1 was positively related to Ki67 and associated with prognostic-related clinical features of OS patients. Overexpression of IDO1 significantly affected the exosome-derived miRNA subsets from MG63, 143B and hFOB1.19 cells. A total of 1244 DE miRNAs were identified, and hsa-miR-23a-3p was further screened as key DE miRNA involved in the progression of OS. GO analysis of target genes of the DE miRNA results showed that target enrichment in the functions of immune regulation and tumor progression. Discussion: Our results indicate that IDO1 has the potential to promote the progression of OS that is related to miRNAs mediated tumor immunity. Targeting IDO1-mediated hsa-miR-23a-3p may be a potential therapeutic strategy for OS treatment.